(untitled) (Torani Journal of Fisheries and Marine Science, 2017)
Tributyltin (TBT) is an organotin compound used as antifouling material for ship or boat paints to prevent attachment of marine biota on the wall of ships or boats. The most dangerous effect of TBT bioaccumulation on marine organisms, particularly gastropods, is the failure on the reproduction system, such as the occurrence of imposex symptoms. The main purposes of this study are to know the histopathology of gonads by species Thais tuberosa and Monodonta labio that has been exposed to imposeks the compound tributyltin (TBT). The sampling of Thais tuberosa and Monodonta labio was conducted at 2 sites: Manado Port and Tateli Coastal Waters. The histopathology test was conducted in the Central Diagnostic Laboratory of Anatomic Pathology, Manado, with Haematoxylin-Eosin (HE) technique. The result showed that histopatology gonads marine gastropods type Thais tuberosa and Monodonta labio there has been a change in the tissues showing the imposex character, if compared with tissues of normal individuals of male and female, but in these changes tissues not cause damage caused by a compound tributyltin (TBT). Keywords : Histopatology of gonad, Gastropods, Imposex, Tributyltin